2011
DOI: 10.1016/j.str.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of HAMP-Mediated Signaling in Transmembrane Receptors

Abstract: HAMP domains mediate signal transduction in over 7500 enzyme-coupled receptors represented in all kingdoms of life. The HAMP domain of the putative archaeal receptor Af1503 has a parallel, dimeric, four-helical coiled coil structure, but with unusual core packing, related to canonical packing by concerted axial rotation of the helices. This has led to the gearbox model for signal transduction, whereby the alternate packing modes correspond to signaling states. Here we present structures of a series of Af1503 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
118
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(133 citation statements)
references
References 22 publications
13
118
0
Order By: Relevance
“…Consistent with a transition between different packing modes, when the volume of a conserved small side chain at a core position (Ala-291 in Af1503 HAMP) was increased by point mutations, the maximal catalytic velocity of the HAMP-CHD chimera decreased (6). Structurally, we recently demonstrated that such substitutions induce a gradual transition in packing of the HAMP domain involving both changes in helix rotation toward a knobs-into-holes packing and changes in bundle shape, consistent with the proposed two-state model (16).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with a transition between different packing modes, when the volume of a conserved small side chain at a core position (Ala-291 in Af1503 HAMP) was increased by point mutations, the maximal catalytic velocity of the HAMP-CHD chimera decreased (6). Structurally, we recently demonstrated that such substitutions induce a gradual transition in packing of the HAMP domain involving both changes in helix rotation toward a knobs-into-holes packing and changes in bundle shape, consistent with the proposed two-state model (16).…”
supporting
confidence: 81%
“…Serine regulation was achieved by substitution of Ala-291 with Phe, supporting the notion of rotation as a potentially common mechanism in HAMP-mediated signal propagation (16). Here we used this Tsr-AC reporter system with the Tsr or Af1503 HAMP domains and carried out a targeted mutational analysis based on sequence and structural features to investigate the role of particular amino acids in signal propagation.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…The authors speculated that the competing Nek2 registers may act as a "toggle" in signal transmission, analogous to the coiled coil in the HAMP domain of Af1503 and the microtubule-binding domain of dynein. In the former, a conformational shift in registers of a tetrameric coiled coil is necessary to transmit signals across a membrane (24,25), and in the latter, helix sliding in the dynein coiled coil is required for communication between the ATPase and microtubule binding domains of dynein (26,27). These toggle signaling mechanisms differ from the capture-and-collapse mechanism we propose for M1 protein.…”
Section: Discussionmentioning
confidence: 74%
“…Attractant-sensitive disulfide bond formation between CheA and receptor suggests that the N-terminal CD1 helices rotate in the PIR on ligand binding (20). Rotations (21,22) and longitudinal shifts of helices (23) within HAMP have been implicated as regulatory switches, and such transitions may interconvert states with different dynamical properties. Long-duration, all-atom molecular dynamics simulations indicate that separations of one KCM N-terminal helix (CD1) and the C-terminal helix of the other subunit (CD2′) are coupled to the flipping of a conserved Phe residue at the receptor tip and that these changes correlate with modification state (24).…”
mentioning
confidence: 99%